The lifestyle of new middle-aged and older adults in Taiwan described by wearable device: age and gender differences. - Wang, Chih-Liang; Li, Cheng-Xue; Liang, Sheng-Fu (European Journal of Ageing, 2024)
Studies of lifestyle through comprehensive objective and subjective measurements of health outcomes are lacking. An examination of lifestyle factors in middle-aged and older adults in terms of age, gender, and the interaction effect of age and gender from physiological and psychological perspectives are imperative. Recent advances in technology such as actigraphy have facilitated objective measurements. This exploratory study contributes to research on age and gender interactions on circadian rhythm, physical activity, sleep, and psychological variables by employing wrist accelerometers to measure behavioral circadian rhythm objectively and by using questionnaires to assess psychological status subjectively. The data were drawn from 218 participants aged 50 and older from the "Middle-aged and older adults Chinese Health and Actigraphy in Taiwan (MOCHA-T)". The results: (1) older adult group is associated with declined physical activity (MVPA time 79.9 min VS. 107.9 min, p =.002), worse sleep efficiency (78.1% VS. 81.9%, p =.008), and earlier lifestyle (Acrophase 14.19 h VS. 14.69 h, p =.01) comparing to middle-aged group. (2) Women have a more regular lifestyle (Interdaily stability 0.6 VS. 051, p < 0.001), higher physical activity (MVPA time 105.7 min VS. 79.3 min, p =.004), and better sleep efficiency (81.6% VS. 77.8%, p =.011) than men. (3) Significant age-by-gender interactions existed in life satisfaction (p =.025), relative amplitude (p =.016), and total wake time (p =.038). Furthermore, aging was associated with significant increases in life satisfaction among men as well as significant decreases in relative amplitude and reductions in the total wake time among women. In conclusion, aging exerted differential effects on life satisfaction in men as well as relative amplitude and the total wake time in women. This result highlights disparities in lifestyle arising from interconnected social and biological challenges.